EXPERIMENTAL STUDY REGARDING THE EFFICIENCY OF THE DIFFERENTIAL TREATMENT IN PHYSICAL EDUCATION LESSON IN THE UPPER SECONDARY EDUCATION (GYMNASIUM, 2017)
Approaching this theme aims the demonstration of some didactic strategies that ensure the increase in physical performances and default students’ grades which will be useful and accessible to every physical education teacher. The modality of differential treatment had accomplished through grouping the students by their availabilities and obtained results, known under the name of level groups. There were made three models of methodological approach for the six assessed abilities/skills, which were the following: running (speed and strength), jumping (long jump with elan), throws (weight throw), specific skills to acrobatic gymnastics and specific skills to the sports game-handball. As a result of the implementation of the experiment during a school year, it can be concluded that the experiment group which has been applied the didactic strategy models based on addressing the educational process through differentiated treatment on value groups, it obtained more than average results at evaluation tests and enhancement higher grades towards the control group.